Estimation of application efficiency of mechanisms of state-private partnership in realization of municipal level projects in the sphere of water supply and sewage - Shevchenko, E. Yu. (Science and Transport Progress, 2012)
In the article the author suggests the approaches to estimation of application efficiency of mechanisms of stateprivate partnership in realization of municipal level projects in the sphere of water supply and sewage; some management actions on improving the application efficiency of the mechanism suggested are determined.